2014
DOI: 10.1002/anie.201403071
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Fluorination Alters the Geometry of a Cyclic Peptide: Exploration of Backbone‐Fluorinated Analogues of Unguisin A

Abstract: New methods for enhancing the efficiency of peptide cyclization, and for fine-tuning the conformations of cyclic peptides, are valuable from a drug development perspective. Herein stereoselective fluorination is investigated as a new strategy for achieving these goals. Four vicinal difluorinated analogues of the natural cyclic heptapeptide unguisin A have been efficiently synthesized. The analogues are found to adopt dramatically different secondary structures, controlled by the fluorine stereochemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
55
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 58 publications
3
55
0
Order By: Relevance
“…Hunter et al demonstrated that vicinal difluorinated g-aminobutyric acid "tethers" can alter the conformation of unguisin analoguec yclic peptides (Figure 24) due to the stereochemical difference of the fluoro-substituents in the tethers, although they did not discuss any biological or physicochemical properties of the peptides containing these tethers. [72] In their study, conformational control depended mainly on the stereoelectronic effects due to the electron-deficient CÀFb onds. It is unclear whether the conformational changeb yt hese fluorinated tethers is dependent on the amino acid sequence.…”
Section: Sequencementioning
confidence: 99%
“…Hunter et al demonstrated that vicinal difluorinated g-aminobutyric acid "tethers" can alter the conformation of unguisin analoguec yclic peptides (Figure 24) due to the stereochemical difference of the fluoro-substituents in the tethers, although they did not discuss any biological or physicochemical properties of the peptides containing these tethers. [72] In their study, conformational control depended mainly on the stereoelectronic effects due to the electron-deficient CÀFb onds. It is unclear whether the conformational changeb yt hese fluorinated tethers is dependent on the amino acid sequence.…”
Section: Sequencementioning
confidence: 99%
“…Among the properties of the CÀFb ond, [5] its capacityt oe ngage in charge-dipole interactions, dipole-dipole interactions, as well as hyperconjugation have all been exploited to fine-tune the conformation of aw ide range of biomolecules including fatty acids, [6] alpha, [7] beta, [8] and gamma [9] amino acids and their oligomers. [11] Based on these precedents andi nv iew of the importance of macrocyclesi nd rug discovery, [12] we becamei nterested in the possibility of using a-fluoroalkoxyaryl groups [13] as a potentialm anifold to increases haped iversity of macrocyclic scaffolds.I ndeed, while in the absence of steric hindrance alkoxyphenyl groups are known to align in the plane of the aryl ring, a-fluoroalkoxyaryl groups ArOCF 2 Ra nd ArOCF 3 have been shown to reduce the in-plane conformational preferences (Fig-ure 1). [10] Furthermore, Hunter and co-workersh ave elegantly demonstrated the pronounced impact that the gauchee ffect of av icinal difluorinated alkyl chain has on the conformation of derivatives of Unguisin A.…”
mentioning
confidence: 99%
“…However, incorporation of two fluoro substituents at the vicinal 2‐ and 3‐positions restricts the number of low‐energy conformations of GABA more severely due to distinct preferences for backbone conformations of the threo and erythro stereoisomers . Although such GABA analogues could be effectively used as peptide foldamers,, the four stereoisomers also showed clearly differentiated biological activity at GABA A‐C receptors, which is remarkable in view of the strong basicity lowering of the amino group by nearby fluoro substituents. Our discussion of the bicyclo[3.2.0]heptane core system adds another potentially interesting case to the list of aliphatic GABA analogues, and its use with different modes of GABA incorporation and the consequent well‐defined conformational fixation could serve as an important tool to unravel preferred interaction modes at the binding sites of target proteins.…”
Section: Resultsmentioning
confidence: 99%